PERBEDAAN KETERAMPILAN BERPIKIR KRITIS DAN HASIL BELAJAR FISIKA ANTARA SISWA YANG PEMBELAJARANNYA MENGGUNAKAN PENDEKATAN KONFLIK KOGNITIF DENGAN PENDEKATAN EKSPOSITORI (Studi Kasus pada Pokok Bahasan Impuls dan Momentum di Kelas XI SMA N 1 Lubuk Sikapin - Emiliannur, Emiliannur; Ratnawulan, Ratnawulan; Hamdi, Hamdi (Jurnal Penelitian Pembelajaran Fisika, 2012)
The background of this research is a lack of physics concept understanding. The students who have not yet successed in applying information and knowledge logically, critically, creatively and innovately when making decisions. One of the solution for this problem is by implementating the cognitive conflict approach. The aims of this research are to: (1) investigate the differences cognitive conflict approach with expository approach to the physics learning achievement; (2) investigate the differences cognitive conflict approach with expository approach to student’s critical thinking skill; (3) investigate the relationship between critical thinking and physics learning achievement. This research was quasi experimental research which used Randomized Control Group Only Design. The population in this research is all of XI IPA SMA N 1 Lubuk Sikaping student listed in the 2010/2011 academic year. Samples were determined using cluster random sampling technique, and elected XI IPA 3 as the first experimental class and XI IPA 1 as the second experimental class. The data is collected through the learning achievement test and critical thinking test, and analyzed by t test and Pearson correlation techniques. The results of data analysis indicate that: (1) there is a significant differences of cognitive conflict approach with expository approach to the physics learning achievement, where the cognitive conflict approach can improve physics learning achievement higher than the expository approach; (2) there is a significant differences of cognitive conflict approach with expository approach to student’s critical thinking skill, where the cognitive conflict approach can improve student’s critical thinking skill higher than the expository approach; (3) there is a significant relationship between critical thinking and physics learning achievement. Keywords: Cognitive Conflict Approach, Expository Approach, Critical Thinking Skill, Physics Learning Achievement.